Perubahan Kotemporer dan Pengunaan Adat pada masyarakat Gayo, Indonesia - Arfiansyah, A. (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2021)
By employing ethnographic methods, this research seeks to provide answer on what has changed in Gayo adat law, particularly after the Aceh government formalized adat law and adat institution? How is the adat being utilized by the Gayonese? What does adat serve for? This paper updates the discourse on Gayonese adat that has been extensively studied by John R. Bowen. Unlike Bowen’s study that focused on adat family law, this article explores both adat family law and adat penal law to observe the development of adat comprehensively. This research was conducted in Gayo society inhabiting both Central Aceh and Bener Meriah district, and it observes a new development of adat that is different from Bowen’s observation. It argues that Adat family law has transformed from being separated from Islam and state (as observed by Bowen) into being integral to the implementation of Islamic teachings in the community. Adat is currently being used to maintain the harmony and unity of kinship. For that purpose, Gayonese makes independent Islamic legal reasonings where conclusion is framed within the context of Islam, although at a glance it appears deviance from the standard Islamic law. Meanwhile, adat penal law which is recently revived by the state is functioned for different purposes by different actors. For activists, adat is important for social transformation, while for the state, adat is used to support legal enforcement at the village.